Analysis of environmental carrying capacity of Beijing-Hangzhou grand canal basin in Zhejiang Province. Issue 3 (May 2019) - Peng, Zhenhua; Xu, Kaiping; Jin, Qiannan; Fu, Lei
Abstract: The harnessing and protection of water environment is critical in the comprehensive treatment of the Beijing-Hangzhou grand canal. Zhejiang section of the canal is located in the Hangjiahu plain, and some parts of the canal are still difficult to reach the water quality requirement. Therefore, it is necessary to investigate and analysis the pollutant discharge and water environment capacity. This paper evaluates the current situation of water environment carrying capacity of grand canal in Zhejiang Province, and puts forward pollution control Strategies. Suggestions are also made based on existing problems.